Fusion. no. 2 Spring rolls - Gallacci, Steve (About Comics, 2015)
"The Tsunami is a cargo ship. Things get put into her, taken across space, and taken out. There's nothing unusual about that. The crew, now that's another matter. Sure Captain Indio Tremaine is human, and so is her first mate, the handsome and indestrucible gambler Dow Cook. But the rest of the crew are genetic constructs of fur, wings and claws. Tan, the engineer, is one wily weael, and that's no metaphor. Together, they are rated "high-risk indy", suited to take on the least likely, most dangerous deliveries. They're the team you want when you have cargo to be delivered and you need things to go right... or when they've already gone wrong. But what if there is no cargo? Then things can go very wrong indeed.